HISTOLOGICAL AND CYTOCHEMICAL STUDIES ON THE EFFECT OF JHA ON BODY WALL, FAT BODY AND MIDGUT EPITHELIUM OF CULEX PIPIENS QUINQUEFASCIATUS SAY - MITTAL, P. K.; ., NAVPIREET (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1998)
Fourth instar larvae (24 h old) were reared in 0.05 ppm and 0.10 ppm if JHA viz. 1- (3'-carbpropoxy phenoxy)-3, 7-dimethyl - 6 -octene, for 24 h alongwith controls. Histological and histochemical studies of cuticle, epidermal cells, fat body cells and midgut epithelium showed necrotic changes after 0.05 and 0.10 ppm. These studies revealed that incomplete moulting and juvenoids (intermoults) formation was due to the interference of JHA in the digestion and absorption of food in the midgut epithelium, biosynthesis and storage of reserves of glycogen, fats and proteins in fat body cells.